Refining contextual inquiry to maximize generalizability and accelerate the implementation process - Davis, Molly; Beidas, Rinad S (Implementation research and practice, 2021)
Background: While contextual inquiry, or in-depth mixed-methods work to study the implementation context, is critical for understanding the setting in which a behavioral health evidence-based practice (EBP) will be implemented, current methods to determine potential barriers and facilitators to implementation are often conducted in a single setting and/or for a single EBP per study, often taking 1–2 years to complete. To maximize generalizability and reduce the research-to-practice gap efficiently, it is important to move toward cross-sector and/or cross-EBP contextual inquiry. Methods: In this viewpoint, we argue for (a) collaborative research studies that seek to identify determinants of implementation that are similar and unique across different settings and EBPs, using rapid approaches when possible; (b) enhanced synthesis of existing research on implementation determinants to minimize duplication of contextual inquiry efforts; and (c) clear rationale for why additional in-depth or rapid contextual inquiry is needed before it is conducted. Throughout this viewpoint, the need to balance scientific rigor and speed are considered. Conclusions: Overall, this viewpoint seeks to encourage researchers to consolidate and share knowledge on barriers and facilitators to implementation to prepare for the scaling out of much needed implementation strategies and interventions for improving health. Plain language summary: Significant time and resources are often devoted to understanding what makes it easier or harder to use best practices for behavioral health concerns in health care settings. The goal of the current viewpoint is to offer ways to streamline this process so that high-quality behavioral health services can reach the patients that need them more quickly. In particular, we advocate for ways to share knowledge among researchers and learn from prior findings to more efficiently identify what makes it easier or harder to use best practices for addressing behavioral health problems in a given setting (e.g., primary care, schools, specialty mental health).